2017
DOI: 10.1016/j.prnil.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased detrusor collagen is associated with detrusor overactivity and decreased bladder compliance in men with benign prostatic obstruction

Abstract: BackgroundThis study aimed to investigate the relationship between detrusor collagen content and urodynamic parameters in men with benign prostatic obstruction.Material and methodsNineteen consecutive patients undergoing open prostatectomy for bladder outlet obstruction (BOO) due to benign prostatic hyperplasia (BPH) were evaluated. Urodynamic tests were performed in all patients. BOO and detrusor contractility were assessed with the BOO index (BOOI) and the bladder contractility index (BCI), respectively. A b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
1
17
0
7
Order By: Relevance
“…Detrusor ECM remodeling is characterized by increased accumulation of collagen and elastic fibers in both the interfascicular and intrafascicular compartments. This finding has been confirmed in several studies using both light and electron microscopy techniques [ 10 , 11 , 15 21 ]. Interestingly, Gilpin et al found that patients with evidence of interfascicular connective tissue infiltration had the highest levels of SMCs mean profile area thus leading the authors to hypothesize that the deposition of connective tissue occurs at a later stage with respect to onset of SMCs hypertrophy [ 10 ].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Detrusor ECM remodeling is characterized by increased accumulation of collagen and elastic fibers in both the interfascicular and intrafascicular compartments. This finding has been confirmed in several studies using both light and electron microscopy techniques [ 10 , 11 , 15 21 ]. Interestingly, Gilpin et al found that patients with evidence of interfascicular connective tissue infiltration had the highest levels of SMCs mean profile area thus leading the authors to hypothesize that the deposition of connective tissue occurs at a later stage with respect to onset of SMCs hypertrophy [ 10 ].…”
Section: Resultssupporting
confidence: 72%
“…Although BOO was not a predictor of increased collagen deposition, patients with reduced bladder compliance and those with a PVR ≥ 200 mL showed a significantly higher C/M [ 20 ]. Similarly, Bellucci et al found a significant negative correlation between C/M and bladder compliance [ 21 ]. Moreover, the probability of urinary retention increased significantly with the C/M.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Bladder remodeling induced by Boo leads to impaired storage and emptying of the bladder, which is characterized by increased collagen accumulation (41,42). increased collagen deposition in the ecM is a key reason for decreased compliance (43,44). Previous studies have reported that pressure promotes an increase in ecM production around BSMcs (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…After BOO, the contractile and nonproliferative phenotype of the BSMCs may transform to a state of synthetic phenotype, results in altered BSMC/ECM interactions, which cause a loss of contractility of BSMCs. Altered ECM composition, especially, Collagens I, III, has been reported in the hypertrophic bladder during the fibrotic stage of hypertrophy .…”
Section: Introductionmentioning
confidence: 98%